Pengaruh Faktor Sosio Demografis terhadap Lama Mencari Kerja bagi Tenaga Kerja Terdidik di Provinsi Sumatera Selatan - Nidatri Mutiah Zatzah; Bambang Suprihatin; Zunaidah Zunaidah (TEMALI : Jurnal Pembangunan Sosial, 2021)
The total workforce in South Sumatra Province is 4,123,669 people, who work 3,942,534 people, and those who are unemployed are 181,135 people if you look at the percentage of the unemployed workforce for the uneducated workforce is 27% while the educated workforce is unemployed by 73%. This study uses secondary data in the form of the 2017 National Labor Force Survey (Sakernas) South Sumatra Province and the use of multiple linear regression analysis (OLS). The results of the analysis of the research that had been conducted stated that the respondents had characteristics, namely that the majority were male at 74%, around 87.4% with a high school / vocational education level, and around 51.1% had work experience. The average respondent was 26.79 years old, had an income of 212 4029.59 rupiah,s and had a long time to look for work 17.31 months. The variables that were not related to the length of time looking for work were age, sex, and education. The variables that have a significant relationship with the length of time looking for work are work experience and income. Each work experience will increase the length of time to look for work in the respondents in South Sumatra Province by 5,132 months.